SC-560 and mofezolac isosteres as new potent COX-1 selective inhibitors with antiplatelet effect - Sisa, Miroslav; Konečný, Lukáš; Temml, Veronika; Carazo, Alejandro; Mladěnka, Přemysl; Landa, Přemysl (Archiv der Pharmazie, 2023)
Selective cyclooxygenase (COX)-1 inhibitors can be employed as potential cardioprotective drugs. Moreover, COX-1 plays a key role in inflammatory processes and its activity is associated with some types of cancer. In this work, we designed and synthesized a set of compounds that structurally mimic the selective COX-1 inhibitors, SC-560 and mofezolac, the central cores of which were replaced either with triazole or benzene rings. The advantage of this approach is a relatively simple synthesis in comparison with the syntheses of parent compounds. The newly synthesized compounds exhibited remarkable activity and selectivity toward COX-1 in the enzymatic in vitro assay. The most potent compound, 10a (IC50 = 3 nM for COX-1 and 850 nM for COX-2), was as active as SC-560 (IC50 = 2.4 nM for COX-1 and 470 nM for COX-2) toward COX-1 and it was even more selective. The in vitro COX-1 enzymatic activity was further confirmed in the cell-based whole-blood antiplatelet assay, where three out of four selected compounds (10a,c,d, and 3b) exerted outstanding IC50 values in the nanomolar range (9-252 nM). Moreover, docking simulations were performed to reveal key interactions within the COX-1 binding pocket. Furthermore, the toxicity of the selected compounds was tested using the normal human kidney HK-2 cell line.
Keywords: molekulární struktura; Cyclooxygenase 2; cyklooxygenasa 2; vztahy mezi strukturou a aktivitou; Humans; simulace molekulového dockingu; lidé; Anti-Inflammatory Agents, Non-Steroidal; Cyclooxygenase 2 Inhibitors; antiflogistika nesteroidní; Structure-Activity Relationship; Molecular Docking Simulation; inhibitory cyklooxygenasy 2; Molecular Structure